Sodium-glucose co-transporter 1 and 2 expression in the mammary artery of patients with bypass surgery: role of the pro-inflammatory response and contribution to oxidative stress. (14th October 2021) - Park, S H; Amissi, S; Algara-Suarez, P; Gong, D S; Mroueh, A; Belcastro, E; Matsushita, K; Bruckert, C; Chaker, A B; Jesel, L; Ohlmann, P; Morel, O; et al.
Abstract: Background: Selective sodium-glucose cotransporter 2 (SGLT2) inhibitors have shown cardiovascular protection independently of glycemic control. Angiotensin II (Ang II) and H2O2 induced the expression of SGLT1 and 2 in cultured endothelial cells and isolated arteries to promote oxidative stress and endothelial dysfunction. However, the expression level and role of SGLT1 and 2 in human arteries remain poorly studied. Purpose: This study examined the expression level of SGLT1 and 2 in the human internal mammary artery (IMA) obtained from bypass surgery patients, and, if so, determined the underlying mechanism and function. Methods: IMAs were obtained from 40 bypass surgery patients (age 45 to 82). The expression level of target factors was assessed by Western blot analysis, immunofluorescence staining and RT-PCR, and the level of oxidative stress using dihydroethidium staining. Human kidney was used as a control tissue known to express SGLT1 and 2. Porcine coronary artery endothelial cells (CAEC) were cultured and studied at passage 1. Results: Western blot analysis of 40 IMA samples indicated a high level of both SGLT1 and 2 in 16 and 17 IMAs, an intermediate level in 8 and 6 IMAs, and a low one in 16 and 17 IMAs, respectively. Immunofluorescence staining of IMA sections indicated that SGLT1 and 2 immunofluorescence signals were observed predominantly in the intima thickening and the media. The expression levels of SGLT1 and 2 were associated with p-p65 NF-kB signals but not angiotensin-converting enzyme (ACE), AT1R, MCP-1, VCAM-1. IMAs with a high expression level of SGLT1 and 2 had a high level of ROS throughout the arterial wall including the intima thickening and endothelium, which was inhibited by the antioxidant N-acetylcysteine, the ACE inhibitor perindoprilat, the AT1R antagonist losartan, and also by the dual SGLT1 and 2 inhibitor sotagliflozin and the selective SGLT2 inhibitor empagliflozin. Pro-inflammatory cytokines mRNA levels of IL-1β, TNF-α and IL-6 were detected in IMAs. Exposure of CAEC to either TNF-α, IL-1β or IL-6 caused a concentration-dependent upregulation of SGLT1 and 2. Conclusion: The present findings indicate that SGLT1 and 2 expression is observed in some but not all IMAs of bypass surgery patients predominantly in the media, the intima thickening and the endothelium. High expression levels of SGLT1 and 2 are associated with NF-kB activation and oxidative stress that is prevented by a selective SGLT2 inhibitor and by a dual SGLT1/2 inhibitor. Since pro-inflammatory cytokines triggered SGLT1 and 2 expression in endothelial cells, the inflammatory burden of patients appears to be an important trigger regulating SGLT1/2 expression and the subsequent pro-oxidant response prompting pro-inflammatory and pro-thrombotic responses. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): This work was supported by an unrestricted research grant from Boehringer Ingelheim Pharma GmbH & Co. KG, Biberach, Germany.